Socio-Economic Factors Influencing Child Labour in Nsukka Local Government Area, Enugu State. - B. N., Akubue; G. U., Anikweze (Journal of Home Economics Research, 2024)
This study investigated factors that cause child labour in Nsukka local government area, Enugu State. Two purposes with two corresponding research questions generated guided the study. The study was survey. The population was 401974 parents. A sample of 2000 parents was randomly selected for the study. Questionnaire was used for data collection. Mean was used for the analysis of data. Findings revealed that both economic and social factors cause child labour in the area of study. The factors include high level of poverty, high unemployment opportunities, low income among parents, marital challenges including separation and divorce among others. Recommendations were made base on the findings, including that job opportunities and awareness on the right of child should be created by the government, non-governmental organizations should open skill acquisition centres to train children especially the orphans and the less privileged in the area of study.